155k views
0 votes
The graph of this function is shifted downwards and the axis of symmetry remains x=1. Which function below the equation of the new graph select all correct answer

The graph of this function is shifted downwards and the axis of symmetry remains x-example-1
User Gringo
by
4.6k points

1 Answer

3 votes

Answer:


y=-x^(2)+2x


y=-x^(2)+2x-4


y=-x^(2)+2x-3

Explanation:

we know that

The equation of a vertical parabola in vertex form is equal to


y=a(x-h)^(2) +k

where

(h,k) is the vertex

The axis of symmetry is equal to the x-coordinate of the vertex

so


x=h

If a> 0 then the parabola open upward (vertex is a minimum)

If a< 0 then the parabola open downward (vertex is a maximum)

In this problem we have


y=-x^(2) +2x+3

The vertex is the point
(1,4) ------> observing the graph

The axis of symmetry is
x=1

If the graph of this function is shifted downwards and the axis of symmetry remains x=1

then

The x-coordinate of the vertex of the new graph must be equal to 1

The y-coordinate of the vertex of the new graph must be less than 4

The parabola of the new graph open downward

therefore

Verify each case

case a)
y=-x^(2)+2x

Convert to vertex form


y=-(x^(2)-2x)


y-1=-(x^(2)-2x+1)


y-1=-(x-1)^(2)


y=-(x-1)^(2)+1

The vertex is (1,1)

therefore

The function could be the equation of the new graph

case b)
y=-x^(2)-2x+3

Convert to vertex form


y-3=-(x^(2)+2x)


y-3-1=-(x^(2)+2x+1)


y-4=-(x+1)^(2)


y=-(x+1)^(2)+4

The vertex is (-1,4)

therefore

The function cannot be the equation of the new graph

case c)
y=-x^(2)+2x-4

Convert to vertex form


y+4=-(x^(2)-2x)


y+4-1=-(x^(2)-2x+1)


y+3=-(x-1)^(2)


y=-(x-1)^(2)-3

The vertex is (1,-3)

therefore

The function could be the equation of the new graph

case d)
y=-x^(2)+2x+4

Convert to vertex form


y-4=-(x^(2)-2x)


y-4-1=-(x^(2)-2x+1)


y-5=-(x-1)^(2)


y=-(x-1)^(2)+5

The vertex is (1,5)

therefore

The function cannot be the equation of the new graph

case e)
y=-x^(2)+2x-3

Convert to vertex form


y+3=-(x^(2)-2x)


y+3-1=-(x^(2)-2x+1)


y+2=-(x-1)^(2)


y=-(x-1)^(2)-2

The vertex is (1,-2)

therefore

The function could be the equation of the new graph

User Andrey Vlasovskikh
by
5.3k points